Three-dimensional interconnected porous graphene coating fiber as well as preparation method and application thereof
By high-temperature treatment of the graphene coating under argon-hydrogen reduction atmosphere, a three-dimensional porous structure was formed, which solved the problems of small specific surface area and insufficient binding capacity of the existing graphene coating materials, and achieved efficient extraction and long-life graphene Coated fibers.
Patent Information
- Application Number
- CN202411501354.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-20
AI Technical Summary
The existing graphene coating materials have small specific surface area, poor adsorption performance, and insufficient binding capacity of the coating to the substrate, resulting in short service life and it is difficult to effectively extract and adsorb contaminants in the conjugated benzene ring structure.
The graphene coating is subjected to high-temperature reduction treatment under a reduction atmosphere composed of argon and hydrogen to form a three-dimensional interconnected porous structure, which significantly improves the specific surface area and lipophilicity of the coating and enhances the binding force with the substrate.
The specific surface area and lipophilicity of the graphene coating are significantly improved, the extraction efficiency and service life of petroleum hydrocarbons are enhanced, and the stable combination of the coating and the substrate is ensured.
Smart Images

Figure CN119162819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene coating materials, and in particular to a three-dimensional interconnected porous graphene coating fiber and a preparation method and application thereof. Background Art
[0002] Solid phase microextraction (SPME) has attracted a lot of attention due to its many advantages, including the integration of sampling, extraction, enrichment, and sample introduction into a single step. This innovative technology has been widely used in a variety of fields, including environmental science, food analysis, forensic science, clinical research, pharmaceuticals, and biology for the detection of a wide range of different analytes. The effectiveness of SPME depends largely on the development of the extraction capacity and durability of the fiber. The extraction capacity is mainly affected by the chemical and physical properties of the coating, while the durability of the fiber is a combination of the mechanical strength, thermal stability, and solvent tolerance of the coating and its supporting material.
[0003] Graphene stands out among SPME coating materials for its large-scale delocalized electron system, excellent specific surface area, and unparalleled thermal, chemical, and mechanical stability. These properties enhance the affinity and overall extraction ability of graphene for benzene ring compounds, allowing graphene-coated fibers to remain durable after undergoing rigorous extraction and desorption processes. A variety of methods have been developed to prepare rGO-coated fibers, from layer-by-layer technology to hydrothermal method, physical deposition, coagulation method, and impregnation method. The traditional impregnation technique is to immerse the substrate in a graphene solution, dry it, and then perform a high-temperature calcination treatment in an air atmosphere to obtain a graphene coating material (reference "Reduced graphene oxide coating with high performancefor the solid phase micro-extraction offurfural in espresso coffee"), but the impregnation is the graphene coating material prepared by the coating with a small specific surface area, poor adsorption performance, and insufficient bonding ability between the coating and the substrate, which easily causes the coating to fall off and reduces the service life.
[0004] The inventor's research group proposed a preparation strategy for reducing and oxidizing graphite oxide on a substrate to form a graphene coating. For example, in Chinese patent CN111569848 A, the research group used graphite oxide as a raw material and ascorbic acid as a reducing agent, reduced the graphite oxide and deposited it on the surface of stainless steel wire in the form of a three-dimensional structure, and then fixed it on the surface of the stainless steel wire by using the water loss and collapse characteristics of the reduced graphene, thereby obtaining a solid phase microextraction fiber with reduced graphene oxide as a coating material. The graphene coating formed by the present invention has good binding ability with the substrate and is not easy to fall off. At the same time, it has excellent extraction and adsorption effects on pollutants with conjugated benzene ring structures. However, the research group also found that the specific surface area and lipophilicity of such graphene-coated fibers still have a certain room for improvement, so further development of graphene-coated fiber materials with high specific surface area and lipophilicity has a high market application prospect. Summary of the invention
[0005] In view of this, the present invention provides a three-dimensional interconnected porous graphene coated fiber and a preparation method thereof. The present invention performs high-temperature reduction treatment on the graphene coating in a reducing atmosphere composed of argon and hydrogen, thereby significantly increasing the specific surface area of the coating, thereby improving the extraction efficiency of the graphene coating for petroleum hydrocarbons.
[0006] The method for preparing the three-dimensional interconnected porous graphene coated fiber of the present invention comprises the following steps:
[0007] S1: mixing graphite oxide and ascorbic acid and dispersing them in deionized water to obtain a graphite oxide dispersion;
[0008] S2: Wipe the metal wire clean and immerse it vertically in the graphite oxide dispersion, heat it at 70°C to 80°C for 0.5h to 1h, take out the metal wire after heating, dry it and set it aside;
[0009] S3: heating the metal wire dried in step S2 to 1000° C. to 1150° C. under a reducing atmosphere to perform a reduction treatment to obtain a three-dimensional interconnected porous graphene coated fiber;
[0010] The reducing atmosphere is a mixed gas of argon and hydrogen in a volume ratio of 3 to 4:1.
[0011] Preferably, the concentration of graphite oxide in the graphite oxide dispersion is 3 mg / mL to 5 mg / mL; the concentration of ascorbic acid is 3 w / v% to 5 w / v%. The graphite oxide of the present invention is prepared by the improved Hummers method, and the specific process is as follows:
[0012] First, 15mL of concentrated sulfuric acid, 5g of potassium persulfate and 5g of phosphorus pentoxide were fully mixed, then heated to 80°C, and 10g of flake graphite was added thereto for pre-oxidation. After the above mixture was cooled to room temperature, it was diluted with 400mL of distilled water, filtered, and washed with distilled water until the pH value of the filtrate became neutral. The product was left to air dry overnight at room temperature. Subsequently, 5g of pre-oxidized graphite and 2.5g of sodium nitrate were added to 120mL of ice-cold concentrated sulfuric acid (ice bath conditions), and then 15g of potassium permanganate was slowly added, and magnetic stirring was performed in an ice bath to ensure that the temperature of the mixture remained below 20°C. Then, the mixture was stirred at 35°C for 2 hours, then 230mL of distilled water was slowly added for dilution, and stirring was continued for 30 minutes. Finally, the reaction was terminated by adding 700mL of distilled water and 12.5mL of 30% hydrogen peroxide. The product was filtered and transferred to a dialysis bag and dialyzed until the pH became neutral and the dialysate was monitored with BaCl2 until no BaSO4 precipitated.
[0013] Preferably, the drying in step S2 is natural drying at room temperature.
[0014] Preferably, the specific method of heating in step S3 is: first keep at 100-120°C for 30 minutes, heat to 300-330°C at a rate of 25-30°C / min and keep for 30 minutes, then heat to 1000-1150°C at a rate of 25-30°C / min.
[0015] Preferably, the reduction treatment time at 1000° C. to 1150° C. in step S3 is 0.5 to 1 h.
[0016] The specific surface area of the graphene coating in the three-dimensional interconnected porous graphene coating fiber prepared by the present invention is 520-550m 2 / g, pore size is 2~10nm.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention forms a three-dimensional cross-linked porous graphene coated fiber material by subjecting the graphene coated fiber to a high-temperature reduction treatment in a mixed atmosphere of argon and hydrogen. The above treatment of the present invention enables the prepared coated fiber to have a higher specific surface area, better lipophilicity, and a stronger bonding force between the coating and the substrate.
[0019] The graphene coated fiber with a three-dimensional cross-linked porous structure prepared by the present invention can efficiently extract petroleum hydrocarbons in the liquid phase, and the graphene coated fiber with a three-dimensional cross-linked porous structure has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1This is a SEM image of the three-dimensional interconnected porous graphene-coated fiber (TDIPrGO) prepared in Example 1;
[0021] Figure 2 This is a SEM photo of the graphene-coated fiber (rGO) prepared in Comparative Example 1;
[0022] Figure 3 C1s spectrum of TDIPrGO prepared in Example 1;
[0023] Figure 4 C1s spectrum of rGO prepared in Comparative Example 1;
[0024] Figure 5 This is the XPS spectrum of TDIPrGO prepared in Example 1;
[0025] Figure 6 This is the XPS spectrum of rGO prepared in Comparative Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with the embodiments.
[0027] Example 1
[0028] A method for preparing a three-dimensional interconnected porous graphene coated fiber (TDIPrGO), the specific steps are as follows:
[0029] S1: 50 mg of graphite oxide and 5 mg of ascorbic acid were mixed and dispersed in 10 mL of deionized water to obtain a graphite oxide dispersion;
[0030] S2: wipe the stainless steel wire with a diameter of 0.15 mm clean and immerse it vertically in the graphite oxide dispersion, heat it at 80°C for 1 hour, take out the stainless steel wire after heating, dry it and set it aside;
[0031] S3: heating the metal wire dried in step S2 to 1100° C. for reduction treatment for 0.5 h under a reducing atmosphere to obtain a three-dimensional interconnected porous graphene coated fiber; wherein the reducing atmosphere is a mixed gas of argon and hydrogen in a volume ratio of 4:1;
[0032] The specific method of heating is: keep at 100°C for 30 minutes, increase to 300°C at 30°C / min and keep for 30 minutes, and increase to 1100°C at 30°C / min and keep for 30 minutes.
[0033] After testing, the specific surface area of the graphene coating in the three-dimensional interconnected porous graphene-coated fiber prepared in Example 1 is 521 m 2 / g, and the average pore size is 3μm.
[0034] The scanning electron micrograph of the three-dimensional interconnected porous graphene coated fiber prepared in Example 1 is as follows: Figure 1 ,in Figure 1 (a) The magnification of the surface image is 100 times. Figure 1 (b) is a cross-sectional image at 300 times magnification. Figure 1 (c) is a surface image at 1000 times magnification.
[0035] Comparative Example 1
[0036] A method for preparing graphene coated fiber (rGO) fiber, the specific steps are the same as those in Example 1, except that the high-temperature reduction treatment under a reducing atmosphere in step S3 is not performed in Comparative Example 1.
[0037] After testing, the specific surface area of the graphene coating in the graphene-coated fiber prepared in Comparative Example 1 is 0.97 m 2 / g, lamellar structure, no pores, SEM photos see Figure 2 ,in Figure 2 (a) The magnification of the surface image is 250 times. Figure 2 (b) The cross-sectional image was magnified 2000 times.
[0038] The materials prepared in Example 1 and Comparative Example 1 were subjected to C1s spectrum and XPS spectrum analysis, wherein Figure 3 C1s spectrum of TDIPrGO prepared in Example 1; Figure 4 C1s spectrum of rGO prepared in Comparative Example 1; Figure 5 This is the XPS spectrum of TDIPrGO prepared in Example 1; Figure 6 This is the XPS spectrum of rGO prepared in Comparative Example 1.
[0039] The C1s electron binding energy of the TDIPrGO prepared in Example 1 and the rGO prepared in Comparative Example 1 is shown in Table 1.
[0040] Table 1
[0041]
[0042] from Figure 5 , 6 As can be seen from Table 1, rGO and TDIPrGO mainly contain C and O elements, and their C / O atomic ratios are 2.3 and 9.2, respectively.
[0043] from Figure 3 , 4Deconvolution of the peaks revealed the presence of CC / C=C, C-OH, OC=O, O=C, and O=C-OH in rGO, while only CC / C=C, C-OH, and OC=O were present in TDIPrGO. More specifically, after AA deoxygenation of GO, the concentrations of C-OH, O=C, and O=C-OH decreased from 47% to 27%, 15% to 2%, and 5% to 2%, respectively. Meanwhile, the concentrations of CC / C=C and OC=O increased from 11% to 30% and 22% to 39%, respectively. The results indicate that C-OH, O=C, and O=C-OH groups can be deoxygenated by AA, but OC=O is difficult to remove under this condition. This result is similar to the results of hydrazine deoxygenation of GO in alkaline medium. After deep deoxygenation by H2 / Ar at high temperature, the concentration of C-OH groups increased from 27% to 59%, while the concentration of OC=O decreased from 39% to 11%. In addition, the O═C and O═C-OH groups were completely removed. These results suggest that C-OH groups may be formed by the ring-opening of residual epoxy groups in a high-temperature hydrogen atmosphere.
[0044] The enrichment factors of TDIPrGO prepared in Example 1 and rGO prepared in Comparative Example 1 for petroleum hydrocarbons (PHCs) were detected, and the results are shown in Table 2.
[0045] Table 2
[0046]
[0047]
[0048] It can be seen from Table 2 that compared with rGO, TDIPrGO coating has better affinity for non-polar PHCs, which further proves that TDIPrGO coating has better lipophilicity.
[0049] The following tests were performed on the TDIPrGO prepared in Example 1:
[0050] Extraction process: 25 mL of water sample (added with 20% (w / v) NaCl) was placed in a 40 mL headspace bottle equipped with a stirrer; the stirring rate was set to 700 rpm; the extraction temperature was 70 °C; the extraction time was 40 min; the thermal desorption temperature was 300 °C; the desorption time was 5 min, and the concentration of each PHCs (C10-C40) was 50 μg L -1 .
[0051] Method Validation:
[0052] The limits of detection (LODs) and limits of quantification (LOQs) were the concentrations of the analytes at signal-to-noise ratios (S / N) of 3 and 10, respectively. Linear regression analysis was performed using peak area versus analyte concentration. The linear range, LODs, LOQs, single fiber, and inter-fiber reproducibility are summarized in Table 3.
[0053] The LODs and LOQs of 31 PHCs were between 1.1 and 29.2 μg / L - 1 and 3.5-62.1 μgL - 1. All PHCs showed good linearity in the concentration range of 5-500μgL-1, with correlation coefficient (R) values greater than 0.991. In the repeatability study, a TDIPrGO-coated fiber was used to measure the concentration of 100μgL-1 under the same conditions. -1 The sample solution of OCPs was extracted three times, and the relative standard deviation (RSD) was less than 6.7%. The RSD of the fiber-to-fiber variation using three different TDIPrGO-coated fibers prepared in the same way was less than 8.2%, indicating that the TDIPrGO-coated fibers were quite stable and the preparation of TDIPrGO-coated fibers was reproducible. These results indicate that the proposed method has good repeatability and high sensitivity in detecting PHCs.
[0054] Table 3
[0055]
[0056]
[0057] The results in Table 3 show that the three-dimensional interconnected porous reduced graphene oxide coated fiber prepared by the present invention has good repeatability and high sensitivity for PHCs detection.
[0058] At 80, 200 and 400 μg L -1 At the same level, the PHCs recovery rate was calculated by the percentage of the amount extracted from the spiked water sample relative to the total spiked amount. The results are shown in Table 4:
[0059] Table 4
[0060]
[0061]
[0062] As can be seen from Table 4, recoveries of 83%-107% were obtained, indicating that this method has high accuracy in determining PHCs in water samples.
[0063] Determination of PHCs in actual water samples:
[0064] PHCs were determined in four real water samples from the Yellow River, a local ditch, South Lake of Yantan Park, and a laboratory using TDIPrGO coated fibers. No detectable PHCs were detected in tap water, and the test results of other water samples are shown in Table 5:
[0065] Table 5
[0066]
[0067]
[0068] C12-24 and C26 were detected in the Yellow River water samples, C12, C13 and C15-31 were detected in the sewage, and C12, C14-21 and C25 were detected in the lake water, with concentrations ranging from 6.6 to 15.6, 5.2 to 48.4 and 5.6 to 15.9 μgL-1, respectively. -1 In addition, two PHCs (C10, C11) were detected in the Yellow River, two (C34, C36) were detected in sewage, and four (C22-24, C28) were detected in lake water samples.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a three-dimensional interconnected porous graphene coated fiber, characterized in that: The following steps are involved: S1: mixing graphite oxide and ascorbic acid and dispersing them in deionized water to obtain a graphite oxide dispersion; S2: Wipe the metal wire clean and immerse it vertically in the graphite oxide dispersion, heat it at 70°C to 80°C for 0.5h to 1h, take out the metal wire after heating, dry it and set it aside; S3: heating the metal wire dried in step S2 to 1000° C. to 1150° C. under a reducing atmosphere to perform a reduction treatment to obtain a three-dimensional interconnected porous graphene coated fiber; The reducing atmosphere is a mixed gas of argon and hydrogen in a volume ratio of 3 to 4:
1.
2. The method for preparing the three-dimensional interconnected porous graphene coated fiber according to claim 1, characterized in that: The concentration of graphite oxide in the graphite oxide dispersion is 3 mg / mL to 5 mg / mL; the concentration of ascorbic acid is 3 w / v% to 5 w / v%.
3. The method for preparing the three-dimensional interconnected porous graphene coated fiber according to claim 1, characterized in that: The drying in step S2 is natural drying at room temperature.
4. The method for preparing the three-dimensional interconnected porous graphene coated fiber according to claim 1, characterized in that: The specific method of heating in step S3 is: first, keep the temperature at 100-120°C for 30 minutes, heat it to 300-330°C at a rate of 25-30°C / min and keep it for 30 minutes, and then heat it to 1000-1150°C at a rate of 25-30°C / min.
5. The method for preparing the three-dimensional interconnected porous graphene coated fiber according to claim 1, characterized in that: The time of reduction treatment at 1000° C. to 1150° C. in step S3 is 0.5 to 1 h.
6. A three-dimensional interconnected porous graphene coated fiber, characterized in that: Prepared by any one of the methods of claims 1 to 5.
7. The use of the three-dimensional interconnected porous graphene coated fiber according to claim 6, characterized in that: The three-dimensional interconnected porous graphene-coated fiber is used for solid phase microextraction of petroleum hydrocarbons in water samples.
